Pengaruh Self-Efficacy dan Pengetahuan Membatk Terhadap Minat Berwirausaha di Bidang Batik Kelas XII Kriya Kreatif Batik dan Tekstil DI SMKN 1 Jabon: Penelitian - Rahma Aisya; Inty Nahari (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The purpose of this study was to determine the effect of self-efficacy on entrepreneurial interest in batik, the effect of batik knowledge on entrepreneurial interest in batik, and to determine the effect of self-efficacy and batik knowledge on entrepreneurial interest in batik among class XII students of Batik and Textile Creative Craft (KKBT) at SMK Negeri 1 Jabon. This research method uses a quantitative method. Samples were taken using saturated sampling techniques with instruments in the form of questionnaires and multiple-choice tests. The results showed that the tendency of self-efficacy and entrepreneurial interest of class XII students of KKBT SMK Negeri 1 Jabon was in the very high category with a percentage of 62% and 65%, as well as batik knowledge in the very good category at a percentage of 70%. Multiple regression showed that the t-test of self-efficacy and batik knowledge was 7.010 > 2.040 and 4.453 > 2.040 at a significance of 0.000 < 0.05. The F count of 192.145 > 3.305 on batik knowledge has an influence on the entrepreneurial interest of XII KKBT students of SMK Negeri 1 Jabon. The R square analysis shows that 0.925 or 92.5% of entrepreneurial interest in the batik sector has an influence on self-efficacy and batik knowledge.